Unicidade de pontos críticos e aplicacão a um problema elíptico quaselinear - Costa, Angélica de Carvalho (2020)
In this work, we study some results that guarantee uniqueness of critical points for a differential Fr´echet functional defined in a normed space and we do an application to a elliptic quasilinear problem that appears in physics. The main tools used in the application are variational methods, namely, minimization arguments, regularity theory and Maximum Principle. We accentuate that the abstract results we present can be applied to a greater number of problems arising from Mathematical Physics.